ROUTE SELECTION FOR PILE DISTRIBUTION AND INTERSECTION PERFORMANCE ANALYSIS ALONG THE ROUTE - I Gusti Raka Purbanto; I Wayan Suweda; I Gede Restu Anggandika (Universitas Udayana, 2025)
The distribution of piles to the installation site requires consideration of various factors, including travel time and route conditions to allow delivery vehicles to maneuver freely. This research aims to determine the optimal time and alternative routes for delivering piles from PT. Satriacipta Astakencana, located at Jl. Prof. Dr. Ida Bagus Mantra Km. 14.5, Sukawati, Gianyar, to the NUGRAA Apartment project site on Jl. Pantai Batu Bolong Canggu. This is due to considerations of distance and delivery time, as well as the frequent traffic conflicts at the unsignalized intersection of Jl. Raya Canggu and Jl. Pantai Berawa. This study uses a method of collecting field survey data, observation, and literature studies. Route selection is based on the shortest distance and fastest time, while the delivery time through the intersection is determined according to the smallest average intersection delay. Based on the analysis, the alternative route via Route 1 from PT. Satriacipta Astakencana - Jl. Gatot Subroto- Jl. Raya Kerobokan - Jl. Raya Canggu - Jl. Pantai Batu Bolong to the delivery location, with a distance of 26.7 km, travel time of 49 minutes, and the selected departure time of 05.00 WITA, is recommended. The analysis shows that the intersection performance during peak hours (07.00-08.00 WITA) has an average delay of 40.42 seconds/smp at intersections I and II. The queue probability at both intersections has exceeded 100% with a level of service of E. Therefore, the suitable time to pass through the intersection is between 05.00-06.00 WITA with an average delay of 10.82 seconds/smp at intersection I and 10.12 seconds/smp at intersection II, with a level of service of B for both intersections..